THE SECOND WORLD WAR IN AMERICAN LITERATURE - Tuychiboeva Shakhlo Zayniddin qizi, Elvina Reshatovna Kenjali (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The Second World War catalyzed a profound transformation in American literature, compelling writers to confront the complexities of human experience amidst the chaos of war. This article examines the diverse voices and narratives that emerged during this tumultuous period, from the gritty realism of Ernest Hemingway to the absurdist satire of Joseph Heller. Through a lens of moral ambiguity and memory, authors grapple with the enduring impact of war on individual and collective consciousness, shedding light on themes of sacrifice, identity, and the quest for belonging. Additionally, the article explores the vital contributions of American women writers such as Virginia Woolf, Anne Frank, and Simone de Beauvoir, whose voices resonate with poignancy and insight, offering unique perspectives on the wartime experience.